The Correlation of MIR‑423 gene polymorphism with Diabetes Miletus type 2 among sample of Iraqi population - Hassan Luqman Mohi Abd Ali; Mohammed Ali Mutasha sabr; Sara Mukls Muhammad Hassan; Mustafa Talib Mohsin Arouid (Genius Journals, 2024)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by persistent hyperglycemia and is associated with serious complications. The risk factors for T2DM include both genetic and lifestyle factors. Genome‑wide association studies have indicated the association of genetic variations with many diseases, including T2DM. Genetic alterations in the MicroRNAs (miRNA s/miRs) are small non‑coding RNA molecules that are involved in the important physiological processes including glucose metabolism. In the present study, the association of MIR‑423 rs6505162 C>A gene poly morphism was studied by using of Tetra primer‑ amplification refractory mutation system‑based polymerase chain reaction (T‑ARMS‑PCR) technique. It was found that demographic features and baseline characteristics it was found that out of the 50 patients, 29 were males and 21 were females. The age range of the patients was 18‑79 years. There was no correlation between age and MIR gene polymorphism in both case and control. Regarding of MIR‑423 rs6505162 C>A genotypes variation with T2DM. The results indicated that there was nonsignificant difference in genotype distribution of the MIR‑423 genotypes polymorphism and T2DM disease after results interpretation between cases and controls regarding genotypes and allelic frequencies. The frequency of CC, CA and AA genotypes was 16 (32.2%), 20(40%) and 14(285 %) for patients, and 17 (44%), 22 (34%)and 11(22%) for the controls, respectively. On the other hand there was no significant relationship between allelic frequencies and T2DM disease.
Keywords: Iraqi population; gene polymorphism; diabetes mellitus